Effect of Tensile and Material Properties on Springback Behavior of DP590 Advanced High Strength Steel During Bending Process - Azam Abdullah, Shahrul; Sani Buang, Muhammad; Azfar Zulkpli, Muhammad; Rozi Mokhtar, Fakhrul; Abdullah, Hashim (International Journal of Engineering and Technology, 2018)
Bending process has been used widely in many industries such as automotive. It is considered as an important process in sheet metal forming. The use of advanced high strength steels in automotive industry has remarkably increased in recent years. Amongst these advanced steels, dual phase steels (DP) have good formability but at the same time springback behavior of this high strength steels also usually increases, which is unfavorable especially after bending and during the assembly processes. Material properties and process parameters are some of contributing factors of the springback behavior. This paper presents an investigation of the uniaxial tensile deformation in transverse (90o), diagonal (45o), and rolling (0o) directions and the effect of material properties of DP590 on springback behavior in bending process. Air V-bending was used for the springback measurements on DP590 specimens with different rolling direction, which is 90°, 45° and 0 and various process parameter values which are die radius and gap, punch radius, thickness, and punch travel. A deformation speed of 25 mm/min was used in this experiment. Tensile test was performed to obtain the value of tensile properties such as young modulus, yield strength, strain hardening coefficient and strength coefficient by analysis stress-strain curve. By adaptive Design of Experiments (DOE) using full factorial, analysis of variance (ANOVA) techniques and Taguchi Method (TM) was chosen as intelligent sampling method to investigate the significant factors contributing to springback behavior. The experimental data shows that the rolling direction, die gap, thickness, punch travel, die radius and punch radius are significant parameters contributing to the springback behavior in the V-die bending of DP590 at the significance level of 0.05. The result form this experiment could be used in improvement of predict the springback behavior and also to understanding the material properties of AHSS in order to eliminate springback and achieve good final product.